Mechanical properties of cross rolled CoCrFeMnNi high entropy alloy - Nakhate A.D.; Kumar N.; Sharma P.; Yadav P.C. (My University, 2025)
In recent years, there has been a significant interest in high-entropy alloys (HEAs) due to their unique compositions, microstructures, and the ability to customize their properties. This study investigated the microstructure and deformation behaviour of the CoCrFeMnNi HEA under homogenised and rolled conditions. Two rolling methods were employed, namely two-step cross-rolling (TSCR) and multi-step cross-rolling (MSCR). Texture analysis revealed the development of Brass (Bs) {1 10} < 112 > and Goss (G) {011} < 100 > texture components in the samples, with an equivalent strain of 1.609. Notably, the MSCR technique involved rotating the samples at a 45° angle around the normal direction (ND) during alternate passes, which was a novel approach in this study. TSCR samples exhibited the formation of dense lamellar bands, while MSCR samples displayed dense dislocations forming a cell block-type structure. Vickers hardness testing revealed differing hardness outcomes as a result of varying deformation levels in samples. Specifically, the TSCR sample with 80% deformation exhibited the highest hardness, while the 50% deformed MSCR sample displayed a comparatively lower hardness. In the context of room-temperature tensile tests, the 80% deformed TSCR sample showed higher ultimate tensile strength but lower ductility. In contrast, the 80% deformed MSCR sample exhibited a slightly lower ultimate tensile strength but higher percentage elongation compared to the TSCR sample. These findings suggest that multi-step cross-rolling can effectively enhance the strength and ductility of HEAs, providing valuable insights for optimizing their mechanical properties. The microstructural and mechanical characterization presented in this study contributes to understanding deformation mechanisms and property optimization strategies in HEAs, thereby supporting their potential applications across various industries. © 2023 Elsevier B.V.